Fishes of the river Padma, Bangladesh: Current trend and conservation status - Joadder, Md. Abdur Razzaq; Galib, Shams Muhammad; Haque, Sk Md. Mohaimenul; Chaki, Nipa (Journal of Fisheries, 2015)
The Padma River is one of the longest rivers and it is believed to be an important spawning and feeding ground for riverine fish species of Bangladesh. This study was conducted from February 2013 to January 2014 and with a view to revealing the diversity of fish fauna in the river. A total of 71 species were recorded belonging to 10 orders, 26 families and 54 genera. The most dominant fish order was Cypriniformes contributing 28 species in 16 genera. Cyprinidae was most dominant family contributing 23 species in 16 genera. Four alien species were found. Twenty eight species have been considered threatened by IUCN Bangladesh. These fishes were belonging to the following categories, Vulnerable (13%), Endangered (18%) and Critically Endangered (8%). Comparing the results with the previous findings, it was revealed that the species diversity have declined in the Padma River over time. Considering all the findings it is concluded that the Padma River could be considered a refuge for conservation of threatened freshwater fishes of Bangladesh. The conservation efforts should ensure minimization of anthropogenic impacts, especially the fishing pressure and introduction of alien invasive species.